Experimental Study on Dynamic Thermal Environment of Capillary Radiant Floor Heating Room with Finite Heat Source. (2017) - Liu, Qinjian; Gao, Yuan; Liang, Fei; Zhao, Xinhui; Jin, Zhenghao; Long, Enshen
Abstract: The heat storage tank has an important role in regulating temporal distribution of solar energy, but its heating characteristics are significantly different from those of the traditional constant heat source system due to the limited heat storage capacity. In order to explore how to effectively utilize the solar energy to improve the indoor thermal environment, a solar heating system (solar flat panel collectors + a heat storage tank + capillary radiation floor) was set up. The dynamic changes regularity of supply water temperature, return water temperature, indoor air temperature and enclosure inner surface temperature were tested during the heating process. The formation mechanism of the dynamic thermal environment was revealed through the theoretical analysis of the comprehensive heating capacity and heat storage capacity of capillary radiation floor. The results show that initial exothermic power of heat storage tank is large but declines rapidly and a 'cliff' temperature reduction of supply water leads to the changes of indoor temperature and wall temperature, which can be divided into three stages, rising, stability and falling. The formation mechanism of the dynamic thermal environment lies in the unique manifestation of the comprehensive heating capacity and the percentage of net radiant heating capacity of floor surface.